Innovation Society Today Perspectives, Fields, and Cases (Springer Fachmedien Wiesbaden : VS, 2018)
The book offers new theoretical perspectives on innovation, analyzes innovation processes in diverse innovation fields, and presents case studies that reflect the diversity of innovations fields. To what extent and in what sense does innovation characterize our societies today? Innovations are no longer limited to the economic sphere; we find them in almost all areas of society today. Diverse actors generate innovations in different, increasingly reflexive ways. New concepts, practices, and institutional forms such as open source, crowdfunding, or citizen panels expand the spectrum. Contents - Perspectives of social theory and theories of society - Innovation fields between economy and culture - Innovation fields between politics, planning, and social movements - Innovation fields between science and public policy Audience Students and scholars of sociology and social theory; economics; political science; cultural sciences; science, technology, and society studies (STS); and innovation studies The Editors Dr. Werner Rammert is professor (em.) of sociology at TU Berlin. Dr. Arnold Windeler is professor of sociology at TU Berlin. Dr. Hubert Knoblauch is professor of sociology at TU Berlin. Dr. Michael Hutter is professor (em.) of sociology at TU Berlin.